Large-mesh high-strength water inlet grid and preparation method thereof

Through the combination of large mesh high-strength water inlet grid design and a variety of high-performance materials, the shortcomings of traditional grids in pressure drop and environmental resistance are solved, and more efficient water treatment and longer equipment service life are achieved.

CN119524642AActive Publication Date: 2025-02-28DELSTAR TECH SUZHOU
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202510087922.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-21
Publication Date
2025-02-28
Estimated Expiration
2045-01-21

AI Technical Summary

Technical Problem

The small mesh design of the existing water inlet grid leads to large resistance, high pressure drop, and large energy loss when the water flow passes, which affects the water treatment efficiency. At the same time, traditional grids perform poorly in high temperature, high pressure and corrosive environments.

Method used

The large mesh high-strength water inlet grid design is used, and the molding is carried out by using a special large mesh design rotary die head in the extruder, and a variety of high-performance resins and reinforced fillers are introduced into the material, combined with plasma spraying technology to apply PTFE and/or FEP coatings.

Benefits of technology

It significantly reduces the pressure drop, improves the water flow smoothness, enhances the mechanical strength, chemical corrosion resistance and heat resistance of the material. It is suitable for a variety of water treatment processes such as reverse osmosis and nanofiltration, and improves the service life and operating efficiency of the equipment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119524642A_ABST
    Figure CN119524642A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of water treatment, and particularly relates to a large-mesh high-strength water inlet grid and a preparation method thereof. A preparation method of the large-mesh high-strength water inlet grid comprises the steps that raw materials are weighed, the raw materials comprise base resin and auxiliaries, and the auxiliaries comprise at least one of a lubricating agent, an antioxidant, a nucleating agent and filler; the method comprises the following steps: adding weighed raw materials into an extruder, melting, mixing and heating the raw materials in the extruder, then carrying out extrusion molding: fully melting and uniformly mixing the materials, integrally molding the materials into a grid product through a special large-mesh design rotary die head, and then cooling and rolling the grid product to obtain the water inlet grid. Wherein the specific parameters of the integrally formed grid product are as follows: the thickness is 20-50mil, the thickness is 20-50mil, the thickness is 20-50mil, and the thickness is 20-50mil; the angle is 30 to 150 degrees; and the mesh area is 10-50mm < 2 >. The grid provided by the invention can meet the rolling process of the existing spiral-wound membrane element, and has the characteristics of low pressure drop, high strength and high filtering efficiency.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of water treatment, and in particular relates to a large-mesh high-strength water inlet grid and a preparation method thereof. Background Art

[0002] As a supporting material, the inlet grid is widely used in the field of water treatment and filtration. In spiral filtration components such as reverse osmosis (RO) and nanofiltration (NF) or flat filtration components such as electrodialysis deionization (EDI), the inlet grid separates the filter membranes, creates a raw water channel, and affects the flow state of the raw water for cross-flow filtration.

[0003] In cross-flow filtration, the configuration and surface properties of the inlet grid will affect the performance of the module, such as flux, desalination rate, etc. In the actual operation of the pressure-driven membrane module, the inlet grid acts as a raw water channel. While improving the flow state of the membrane surface, it will also cause pressure loss due to the steric effect. The difference between the raw water inlet pressure and the concentrated water pressure at the end of the module is usually called pressure drop.

[0004] In practical applications, the size of membrane components is fixed. In water treatment applications, 8040 membrane elements are the mainstream, that is, the diameter of the membrane element is 203.2mm (80 / 10 inch) and the length is 1016mm (40 inch). The raw materials that make up the membrane element are mainly filter membrane, water inlet grid, and water production grid. The three are sealed under the action of adhesive to form a basic unit; under the fixed membrane element diameter, different numbers of membrane units need to be packaged.

[0005] Generally, the thickness of the water inlet grid used in industrial membrane elements ranges from 20-40 mils. A water inlet grid that is too thin cannot provide sufficient raw water channels, resulting in a large pressure drop and easy fouling. A water inlet grid that is too thick will result in a low effective area of ​​the rolled membrane and limited water production flux. Traditional water inlet grids have small meshes and a dense design of longitude and latitude nodes, which can provide excellent support, but often bring additional raw water resistance, large energy loss, and low net driving force for water production, resulting in high overall energy consumption and high operating costs for membrane elements and membrane systems. Summary of the invention

[0006] The present invention aims at the deficiencies of the prior art, provides a large-mesh high-strength water inlet grid, and provides a method for preparing the water inlet grid. Furthermore, multiple deformation modes are provided based on the method.

[0007] The technical solution of the present invention is as follows: A large-mesh high-strength water inlet grid, the water inlet grid is prepared by the following steps: Weighing raw materials, the raw materials include base resin and additives, the additives include at least one of lubricant, antioxidant, nucleating agent and filler; The weighed raw materials are added to the extruder, melted, mixed and heated, and then extruded into shape: after the materials are fully melted and mixed, they pass through a specially designed large-mesh rotary die head to be integrally formed into a grid product, and then go through cooling and winding processes to obtain a water inlet grid; Among them, the specific parameters of the grid product formed into one piece through a specially designed large mesh rotary die include: Thickness: 20-50mil; Angle: 30-150°; Mesh area: 10-50mm 2 ; In many embodiments, the temperature of the melt mixing and heating in the extruder is controlled at 200-300°C.

[0008] Regarding raw materials: further, by weight, base resin 80-110 parts; lubricant 0-0.5 parts; antioxidant 0.1-0.5 parts; nucleating agent 0-5.0 parts; filler 0-10 parts.

[0009] Furthermore, the base resin includes at least one of PP resin, HDPE resin, PVDF, PFA, and PEEK, the lubricant includes PE wax, the antioxidant includes a hindered phenol antioxidant, and the filler includes at least one of talc powder, boron nitride nanosheets, and chopped fibers.

[0010] Furthermore, the raw material also includes a silane coupling agent, and the antioxidant includes at least one of antioxidant 1010 and antioxidant 168.

[0011] Regarding the preparation method: further, when the weighed raw materials are added into the extruder, different temperature sections of 260-320°C are set, the base resin is blended, and then the remaining raw materials are added in the mixing stage, and the extruder is melt-mixed and heated, and then extruded and molded: after the materials are fully melted and mixed, they pass through a specially designed large-mesh rotary die head to be integrally molded into a grid product, and then through cooling and winding processes, a water inlet grid is obtained.

[0012] Regarding the coating: Furthermore, the preparation step also includes: after extrusion molding, applying a coating on the surface of the water inlet grid: using plasma spraying equipment to spray the coating solution on the water inlet grid, after spraying, curing the water inlet grid at 100-150°C for 20-60 minutes to obtain a finished grid.

[0013] Furthermore, the coating solution includes at least one of PTFE, a fluorinated solvent, an accelerator, NMP, FEP, and a dispersant.

[0014] Further, the coating solution includes coating solution 1 and coating solution 2, Mix PTFE and fluorinated solvent, stir evenly, add accelerator, and stir to obtain coating solution 1; Heat NMP to 150-180° C., gradually add FEP, stir, add accelerator, then add dispersant, stir, slowly cool the uniformly mixed solution to room temperature at 80-100° C., stirring during the process, to obtain coating solution II.

[0015] Furthermore, after extrusion molding, a coating is applied to the surface of the water inlet grid: a coating solution 1 is sprayed on the water inlet grid using a plasma spraying device, and after spraying, the water inlet grid is cured at 100-150°C for 20-60min to obtain a cured grid; a coating solution 2 is sprayed on the cured grid using a plasma spraying device, and after spraying, the water inlet grid is cured at 100-150°C for 20-60min to obtain a finished grid.

[0016] Compared with the prior art, the present invention has the following beneficial effects: 1. Reduce pressure drop and improve fluidity: Although the traditional small-mesh grid has strong supporting force, due to the small mesh area, the water flow has a large resistance when passing through the grid, which is easy to produce high pressure drop, resulting in large energy loss and affecting water treatment efficiency. The large-mesh water inlet grid designed by the present invention has a mesh area increased to 10-50 mm² (the traditional mesh area is <10 mm²), which significantly improves the patency of water flow, effectively reduces pressure drop, increases the net driving force and water production flux of membrane elements, and reduces operating costs. For example, the water inlet grid prepared in Examples 1-6 has significantly increased thickness and mesh area, but the performance test performance is excellent, the pressure drop is significantly reduced, and at the same time, it maintains better stiffness and tensile breaking force, and can effectively withstand the spiral membrane assembly and high-pressure filtration conditions. In addition, the grid of the present application can meet the rolling process of existing rolled membrane elements, which has many difficulties, such as: how to balance parameters such as the mesh area and thickness of the grid; how to ensure that the grid has the advantages of low pressure drop, high strength and high filtration efficiency while balancing multiple parameters of the grid; the comprehensive cost also needs to be considered, for example: an increase in thickness will increase the cost and may also affect the fluidity.

[0017] 2. The present application also optimizes the formula: the present invention uses PP, HDPE, PVDF, PFA and PEEK multiple high-performance resins to blend the matrix, combined with reinforcing fillers such as boron nitride nanosheets and chopped fibers, to optimize the mechanical properties of the material, especially the stability under high temperature, high pressure and corrosive environments. The synergistic effect between different polymers forms a good combination of mechanical properties. The reasonable combination of different materials and fillers forms a microstructure with high crystallinity, which improves the overall performance of the material.

[0018] 3. The present invention introduces polymers into the material and applies PTFE and / or FEP coatings on the material surface by plasma spraying technology, which effectively prevents the penetration and erosion of chemical substances into the material matrix. The acid and alkali resistance and hydrolysis resistance are greatly improved.

[0019] 4. The grid prepared by the mesh design, material combination and coating technology of the present invention has excellent mechanical strength, chemical corrosion resistance, heat resistance, biological pollution control, water flow resistance and many other aspects. It can withstand high temperature, high pressure and strong acid and alkali environment, can be used as a supporting structure material, and can also be suitable for high-efficiency filtration in various water treatment processes such as reverse osmosis (RO) and nanofiltration (NF). Especially for some highly polluting and highly corrosive industrial wastewater treatment conditions, it can greatly improve the service life and operation efficiency of the equipment.

[0020] More detailed principles are described in detail in the specific implementation manner in conjunction with examples and comparative examples. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] The accompanying drawings are used to provide further understanding of the present invention and constitute a part of the specification. They are used to explain the present invention together with the embodiments of the present invention and do not constitute a limitation of the present invention.

[0022] In the attached picture: Figure 1 This is a high-definition microscope image of the grid of Comparative Example 1 of the present invention magnified 20 times; Figure 2 This is a high-definition microscope image of the grid magnified 20 times according to Example 1 of the present invention; Figure 3 This is a high-definition microscope image of the grid magnified 20 times according to Example 2 of the present invention; Figure 4 The voltage drop test equipment of the present invention is shown in FIG. DETAILED DESCRIPTION

[0023] In order to better illustrate the purpose, technical scheme and advantages of the present invention, the present invention will be further described below in conjunction with the accompanying drawings and specific embodiments. The experimental methods used below are conventional methods unless otherwise specified, and the materials, reagents, etc. used are all commercially available unless otherwise specified.

[0024] 1. Preparation of large mesh and high strength water inlet grid Method 1: The present application provides a method for preparing a large-mesh, high-strength water inlet grid, and the specific steps are as follows: 1. Weigh the raw materials: by weight, base resin 80-110 parts; lubricant 0.1-0.5 parts; antioxidant 0.1-0.5 parts; nucleating agent 0.1-5.0 parts; filler 0-10 parts. The base resin includes PP resin and HDPE resin.

[0025] 2. Add the weighed raw materials into the main material hopper of the extruder, control the melting and mixing heating temperature of the extruder at 200-300℃, and then extrude and shape: after the materials are fully melted and mixed, they pass through a specially designed large-mesh rotary die head to be integrally formed into a grid product, and then go through cooling and winding processes to complete the preparation of the product.

[0026] Among them, the specific parameters of the grid product formed into one piece through a specially designed large mesh rotating die are: (1) The grid configuration, including thickness, angle, and mesh area, is of great significance to the pressure drop of the grid and membrane elements.

[0027] The grid configuration of this application: Thickness: 20-50mil Angle: 30-150° Mesh area: 10-50mm 2 It should be noted that the mesh area of ​​the traditional grid is less than 10mm 2 .

[0028] (2) Grid strength, including grid stiffness and tensile breaking force, is of great significance for membrane element rolling and high-pressure applications.

[0029] The grid stiffness of the present application is: 0.8-2.8 mN·m; the grid tensile breaking force is: 10-50N.

[0030] Among them, the special large mesh rotary die head is independently designed and manufactured by Dexing Technology (Suzhou) Co., Ltd. The company number / model of the special large mesh rotary die head is 3554-C-35, which can be purchased by number / model.

[0031] Provide specific examples and comparative examples below: Referring to Table 1, Examples 1-6 and Comparative Examples 1-2 were prepared. The preparation methods of Examples 1-6 were similar to those of Method 1.

[0032] Preparation method of comparative example 1: feed the raw materials into the main feed port of a single screw extruder, set the heating temperature of the extruder screw to 250°C, and then extrude and mold: the melt passes through a traditional small mesh rotary die head to be molded into a grid product.

[0033] Preparation method of comparative example 2: feed the raw materials into the main feed port of a single screw extruder, set the heating temperature of the extruder screw to 230°C, and then perform extrusion molding: the melt passes through a traditional small mesh rotary die head to be molded into a grid product.

[0034] The specific parameters of the traditional small mesh rotary die head are: (1) Grid configuration: Thickness: 20-40mil Angle: 30-150° Mesh area <10mm 2 (2) Grid strength: Grid stiffness: 0.8-2.8 mN·m; Grid tensile breaking force: 10-20N.

[0035] Among them, the traditional small mesh rotary die head is independently designed and manufactured by Dexing Technology (Suzhou) Co., Ltd. The company number / model of the traditional small mesh rotary die head is 3554-C-30, which can be purchased by number / model.

[0036] Table 1

[0037] The manufacturer brands in Table 1 are as follows: The manufacturer of PP resin is Taiwan Plastics Industrial Co., Ltd., and the brand is Yungsox 1040; The manufacturer of HDPE resin is Shanghai Secco Petrochemical Co., Ltd., and the brand is HD 5502; The manufacturer of PE wax is Honeywell International, and the brand is A-C8; The antioxidant was produced by BASF China and its brand name was Irganox 1010; The manufacturer of the nucleating agent is Dongguan Baoxu Chemical Technology Co., Ltd., and the brand is BX NA 900; The manufacturer of the filler is Suzhou Youkuangsu New Materials Co., Ltd. and the brand name is ML-30S400B.

[0038] The products (grids) of Examples 1-6 and Comparative Examples 1-2 are tested in the following manner: 1. Thickness test: Use Mitutoyo thickness gauge to test the average thickness of 20 different areas as the grid thickness, the unit is mil, which is one thousandth of an inch; 2. Angle test: Use a protractor to test the values ​​at three different positions according to the grid machine direction, and take the average value as the grid angle in degrees; 3. Mesh area: Under the KEYENCE high-definition microscope, the computer measures the length of the mesh longitude and latitude a, and calculates the mesh area by combining the mesh angle α, that is, a 2 × sinα; 4. Stiffness test: The grid needs to be left in a constant temperature (23±2℃) and constant humidity (50±10%) environment for 24 hours, and then the stiffness value of the grid is tested using a stiffness tester according to the reference standard GB / T 22364-2018; 5. Tensile test: The grid needs to be placed in a constant temperature (23±2℃) and constant humidity (50±10%) environment for 24 hours, and then a universal testing machine is used to test the tensile breaking force of the grid, with reference to the standard GB / T 1040.2-2022 and a tensile speed of 50mm / min; 6. Voltage drop test: refer to Figure 4 , using STERLITECH membrane pool, by testing the grid inlet pressure value p1 and outlet pressure value p2, calculate the grid pressure drop at a flow rate of 2L / min, that is, Δp=p1-p2.

[0039] See Table 2 for the results.

[0040] Table 2

[0041] Also, please refer to Figure 1-3 The present application also provides high-definition microscope photos of Comparative Example 1, Example 1, and Example 2 magnified 20 times, which can clearly show the differences between the products.

[0042] Analysis: The water inlet grid prepared in Example 1-6 has significantly increased thickness and mesh area, but the performance test shows excellent performance, the pressure drop is significantly reduced, and at the same time, the stiffness and tensile breaking force are maintained.

[0043] (II) Further optimization of the preparation method Example 7 In this example, the formula is optimized and the specific preparation steps are as follows: 1. Weigh the raw materials: by weight: 70 parts of polyvinylidene fluoride (PVDF), 15 parts of perfluoroalkoxyethylene (PFA), 10 parts of polyetheretherketone (PEEK), 3 parts of boron nitride nanosheets, 5 parts of chopped fibers, 1 part of silane coupling agent (KH550), and antioxidant combination (antioxidant 1010: 0.2 parts, antioxidant 168: 0.3 parts).

[0044] 2. Use a twin-screw extruder and set different temperature sections (260-320℃), blend PVDF, PFA and PEEK in sequence at 260℃, then add boron nitride nanosheets, chopped fibers and antioxidant combination at 280℃ in the mixing stage, and add silane coupling agent for interface enhancement treatment. The melt mixing heating temperature of the extruder is controlled at 300℃, and then extrusion molding is performed at 320℃: after the materials are fully melted and mixed, they pass through a specially designed large mesh rotary die head to be integrally molded, and then go through cooling and winding processes to obtain a grid.

[0045] The specific parameters of the one-piece molding are the same as those of method 1 through a specially designed rotary die with large mesh holes.

[0046] Example 8 In this example, the process is optimized and the specific preparation steps are as follows: 1. Weigh the raw materials: by weight: 70 parts of polyvinylidene fluoride (PVDF), 15 parts of perfluoroalkoxyethylene (PFA), 10 parts of polyetheretherketone (PEEK), 3 parts of boron nitride nanosheets, 5 parts of chopped fibers, 1 part of silane coupling agent (KH550), and antioxidant combination (antioxidant 1010: 0.2 parts, antioxidant 168: 0.3 parts).

[0047] 2. Extrusion molding: Use a twin-screw extruder and set different temperature sections (260-320℃), blend PVDF, PFA and PEEK in sequence at 260℃, then add boron nitride nanosheets, chopped fibers and antioxidant combination at 280℃ in the mixing stage, and add silane coupling agent for interface enhancement treatment. The melt mixing heating temperature of the extruder is controlled at 300℃, and then extrude at 320℃: after the materials are fully melted and mixed, they pass through a specially designed large mesh rotary die head to be integrally formed, and then go through a cooling process to obtain a grid.

[0048] The specific parameters of the one-piece molding are the same as those of method 1 through a specially designed rotary die with large mesh holes.

[0049] 3. After extrusion molding, apply a coating on the surface of the material through a plasma spraying process. Ensure the uniformity and adhesion of the coating. Specifically: Mix PTFE particles (particle size 0.5-1μm) with fluorinated solvent in a weight ratio of 1:5, stir evenly, add 1 part of accelerator, and stir to obtain coating solution 1. Use plasma spraying equipment to spray coating solution 1 on the grid, spraying pressure: 0.3 MPa, spraying distance: 20 cm, spraying speed: 0.5 m / s, coating thickness: controlled at 3-5μm, after spraying, place the grid in an oven and cure at 130°C for 30 minutes to obtain a finished grid.

[0050] The finished grid can be further cooled and rolled up as required.

[0051] Example 9 In this embodiment, composite coating is performed, which is different from embodiment 8, and step 3 is: 3. After extrusion molding, apply a composite coating on the surface of the material through a plasma spraying process. Ensure the uniformity and adhesion of the coating. Specifically: Mix PTFE particles (particle size 0.5-1μm) and fluorinated solvent in a weight ratio of 1:5, stir evenly, add 1 part of accelerator, and stir to obtain coating solution 1. Use plasma spraying equipment to spray coating solution 1 on the grid, spraying pressure: 0.3 MPa, spraying distance: 20 cm, spraying speed: 0.5 m / s, coating thickness: controlled at 3-5μm, after spraying, place the grid in an oven and cure at 130°C for 30 minutes to obtain a cured grid.

[0052] Heat N-methylpyrrolidone (NMP) to 150-180°C, gradually add fluorinated ethylene propylene (FEP) powder (particle size less than 20 μm), keep stirring at high speed for 30-60 minutes, add 0.5 parts of accelerator, and then add 0.2 parts of dispersant (polyvinylpyrrolidone, PVP), stir, and slowly cool the mixed solution to room temperature at 80-100°C while stirring to obtain coating solution II.

[0053] Use plasma spraying equipment to spray the second coating solution onto the cured grid, spraying pressure: 0.25 MPa, spraying distance: 25 cm, spraying speed: 0.4 m / s, coating thickness: controlled at 2-3 μm. After spraying, place the grid material in an oven and cure it at 150°C for 20 minutes to obtain a finished grid.

[0054] The remaining steps are the same as those in Example 8.

[0055] Example 10 In this embodiment, PP resin is added, and the specific preparation steps are as follows: 1. Weigh the raw materials: by weight: 60 parts of PP resin, 10 parts of polyvinylidene fluoride (PVDF), 5 parts of perfluoroalkoxyethylene (PFA), 10 parts of polyetheretherketone (PEEK), 3 parts of boron nitride nanosheets, 5 parts of chopped fibers, 1 part of silane coupling agent (KH550), and antioxidant combination (antioxidant 1010: 0.2 parts, antioxidant 168: 0.3 parts).

[0056] 2. Use a twin-screw extruder and set different temperature sections (260-320℃), blend PVDF, PFA, PEEK and PP resins in sequence at 260℃, then add boron nitride nanosheets, chopped fibers and antioxidant combination at 280℃ in the mixing stage, and add silane coupling agent for interface enhancement treatment. The melt mixing heating temperature of the extruder is controlled at 300℃, and then extrusion molding is performed at 320℃: after the materials are fully melted and mixed, they pass through a specially designed large mesh rotary die head to be integrally molded, and then go through cooling and winding processes to obtain a grid.

[0057] The specific parameters of the one-piece molding are the same as those of method 1 through a specially designed rotary die with large mesh holes.

[0058] It should be noted that the processing temperature of the PP resin alone is relatively low. In order to avoid degradation of the PP resin, the present application blends and modifies the PP resin and sets a specific blending order.

[0059] Embodiment 11 In this embodiment, PP resin and HDPE resin are added, and the specific preparation steps are as follows: 1. Weigh the raw materials: by weight: 60 parts of PP resin, 20 parts of HDPE resin, 10 parts of polyvinylidene fluoride (PVDF), 5 parts of perfluoroalkoxyethylene (PFA), 10 parts of polyetheretherketone (PEEK), 3 parts of boron nitride nanosheets, 5 parts of chopped fibers, 1 part of silane coupling agent (KH550), and antioxidant combination (antioxidant 1010: 0.2 parts, antioxidant 168: 0.3 parts).

[0060] 2. Use a twin-screw extruder and set different temperature sections (260-320℃), blend PVDF, PFA, PEEK, PP resin, and HDPE resin in sequence at 260℃, then add boron nitride nanosheets, chopped fibers, and an antioxidant combination at 280℃ in the mixing stage, and add a silane coupling agent for interface enhancement treatment. The melt mixing heating temperature of the extruder is controlled at 300℃, and then extrusion molding is performed at 320℃: after the materials are fully melted and mixed, they pass through a specially designed large-mesh rotary die head for one-piece molding, and then go through cooling and winding processes to obtain a grid.

[0061] The specific parameters of the one-piece molding are the same as those of method 1 through a specially designed rotary die with large mesh holes.

[0062] Example 12 In this embodiment, polyvinylidene fluoride (PVDF) and perfluoroalkoxyethylene (PFA) are not added, and the specific preparation steps are as follows: 1. Weigh the raw materials: by weight: 60 parts of PP resin, 20 parts of HDPE resin, 10 parts of polyetheretherketone (PEEK), 3 parts of boron nitride nanosheets, 5 parts of chopped fibers, 1 part of silane coupling agent (KH550), and antioxidant combination (antioxidant 1010: 0.2 parts, antioxidant 168: 0.3 parts).

[0063] 2. Use a twin-screw extruder and set different temperature sections (260-320℃), blend PEEK, PP resin and HDPE resin in sequence at 260℃, then add boron nitride nanosheets, chopped fibers and antioxidant combination at 280℃ in the mixing stage, and add silane coupling agent for interface enhancement treatment. The melt mixing heating temperature of the extruder is controlled at 300℃, and then extrusion molding is performed at 320℃: after the materials are fully melted and mixed, they pass through a specially designed large mesh rotary die head to be integrally molded, and then go through cooling and winding processes to obtain a grid.

[0064] The specific parameters of the one-piece molding are the same as those of method 1 through a specially designed rotary die with large mesh holes.

[0065] Embodiment 13 In this embodiment, polyvinylidene fluoride (PVDF), perfluoroalkoxyethylene (PFA) and polyetheretherketone (PEEK) are not added, and the specific preparation steps are as follows: 1. Weigh the raw materials: by weight: 60 parts of PP resin, 20 parts of HDPE resin, 3 parts of boron nitride nanosheets, 5 parts of chopped fibers, 1 part of silane coupling agent (KH550), and antioxidant combination (antioxidant 1010: 0.2 parts, antioxidant 168: 0.3 parts).

[0066] 2. Use a twin-screw extruder and set different temperature sections (260-320℃), blend PEEK, PP resin and HDPE resin in sequence at 260℃, then add boron nitride nanosheets, chopped fibers and antioxidant combination at 280℃ in the mixing stage, and add silane coupling agent for interface enhancement treatment. The melt mixing heating temperature of the extruder is controlled at 300℃, and then extrusion molding is performed at 320℃: after the materials are fully melted and mixed, they pass through a specially designed large mesh rotary die head to be integrally molded, and then go through cooling and winding processes to obtain a grid.

[0067] The specific parameters of the one-piece molding are the same as those of method 1 through a specially designed rotary die with large mesh holes.

[0068] Embodiment 14 In this embodiment, no boron nitride nanosheets are added, and the specific preparation steps are as follows: 1. Weigh the raw materials: by weight: 60 parts of PP resin, 20 parts of HDPE resin, 10 parts of polyvinylidene fluoride (PVDF), 5 parts of perfluoroalkoxyethylene (PFA), 10 parts of polyetheretherketone (PEEK), 5 parts of chopped fibers, 1 part of silane coupling agent (KH550), and antioxidant combination (antioxidant 1010: 0.2 parts, antioxidant 168: 0.3 parts).

[0069] 2. Use a twin-screw extruder and set different temperature sections (260-320℃), blend PVDF, PFA, PEEK, PP resin, and HDPE resin in sequence at 260℃, then add chopped fibers and an antioxidant combination at 280℃ in the mixing stage, and add a silane coupling agent for interface enhancement treatment. The melt mixing heating temperature of the extruder is controlled at 300℃, and then extrusion molding is performed at 320℃: after the materials are fully melted and mixed, they pass through a specially designed large-mesh rotary die head for one-piece molding, and then go through cooling and winding processes to obtain a grid.

[0070] The specific parameters of the one-piece molding are the same as those of method 1 through a specially designed rotary die with large mesh holes.

[0071] Embodiment 15 In this example, no chopped fibers are added, and the specific preparation steps are as follows: 1. Weigh the raw materials: by weight: 60 parts of PP resin, 20 parts of HDPE resin, 10 parts of polyvinylidene fluoride (PVDF), 5 parts of perfluoroalkoxyethylene (PFA), 10 parts of polyetheretherketone (PEEK), 3 parts of boron nitride nanosheets, 1 part of silane coupling agent (KH550), and antioxidant combination (antioxidant 1010: 0.2 parts, antioxidant 168: 0.3 parts).

[0072] 2. Use a twin-screw extruder and set different temperature sections (260-320℃), blend PVDF, PFA, PEEK, PP resin, and HDPE resin in sequence at 260℃, then add boron nitride nanosheets and antioxidant combination at 280℃ in the mixing stage, and add silane coupling agent for interface enhancement treatment. The melt mixing heating temperature of the extruder is controlled at 300℃, and then extrusion molding is performed at 320℃: after the materials are fully melted and mixed, they pass through a specially designed large-mesh rotary die head to be integrally molded, and then go through cooling and winding processes to obtain a grid.

[0073] The specific parameters of the one-piece molding are the same as those of method 1 through a specially designed rotary die with large mesh holes.

[0074] The manufacturer's brands of Examples 7-15 are as follows: PP resin: Taiwan Plastics Industrial Co., Ltd., Yungsox 1040; HDPE resin: Shanghai Secco Petrochemical Co., Ltd., HD 5502; Polyvinylidene fluoride (PVDF): Arkema, Kynar 740; Perfluoroalkoxyethylene (PFA): DuPont, USA, PFA 450HP; Polyetheretherketone (PEEK): Victrex, 450G; Boron nitride nanosheets: Suzhou Napu Material Technology Co., Ltd., NS-BN, 98.0% purity; Silane coupling agent (KH550): Shanghai Hongshun Biotechnology Co., Ltd., 98.0% purity; Antioxidant 1010 and antioxidant 168 were purchased from BASF China; PTFE microparticles (particle size 0.5-1 μm): AGC Chemicals Company, Fluon; Fluorinated solvent: 3M Company, Novec 7100 electronic fluorinated liquid; Accelerator: 3M Company, Novec FC-4432; N-Methylpyrrolidone (NMP) was purchased from Aladdin Reagents with 99% purity; Fluorinated ethylene propylene (FEP) powder (particle size less than 20 μm) was purchased from 3M Company, Dyneon; Dispersant (polyvinylpyrrolidone, PVP): BASF China, Kollidon 30; Chopped fiber: Owens Corning, CS415, chopped length 4 mm.

[0075] The grids of Examples 7-15 are tested below, and the testing method is as follows: Chemical resistance test: 1. Acid and alkali corrosion resistance test: Method: The samples were immersed in 10% H2SO4 solution, 10% NaOH solution and 10% NaCl solution at room temperature for 7 days, and the changes in surface and mechanical properties were observed.

[0076] Objective: Each embodiment should have no significant weight loss and mechanical property degradation after immersion (weight loss ≤ 1%, tensile breaking force reduction ≤ 5%).

[0077] 2. Hydrolysis resistance test: Method: The sample was immersed in a water bath at 95°C for 72 hours, and the tensile breaking force before and after immersion was tested.

[0078] Target: The variation of tensile breaking force of each example is ≤5%.

[0079] Tensile breaking force: A universal testing machine was used, with reference to standard GB / T 1040.2-2022, and a tensile speed of 50 mm / min to test the tensile breaking force of the grid.

[0080] Please refer to Tables 3 and 4 for the results.

[0081] Table 3 Acid and alkali corrosion resistance test results

[0082] Table 4 Hydrolysis resistance test results

[0083] analyze: In Example 7, a combination of polyvinylidene fluoride (PVDF), perfluoroalkoxyethylene (PFA) and polyetheretherketone (PEEK) is used. These high-performance polymers can form a highly crystalline structure in the composite material, and have excellent chemical resistance and heat resistance, especially in harsh environments. Example 7 provides a new formula, and the components are compounded to form a highly crystalline polymer network structure, which effectively enhances the acid, alkali and hydrolysis resistance of the material. The addition of boron nitride nanosheets further improves the thermal conductivity and mechanical properties of the material, and also enables it to have higher creep resistance and aging resistance.

[0084] In Example 8, a plasma spraying process is introduced to form a coating on the surface of the material. The coating has excellent corrosion resistance and low surface energy, can significantly reduce the surface energy of the material, and make the material more stable in an acid-base environment. The coating forms a chemical barrier on the surface of the material to prevent acid and base substances from corroding the internal structure of the material. The interaction between the fluorinated solvent and the PTFE particles further improves the adhesion and durability of the coating.

[0085] In Example 9, in this example, the composite coating of PTFE and FEP combines the advantages of both. The structure of the composite coating can effectively reduce the generation of micropores on the surface of the material, thereby having higher acid and alkali corrosion resistance and hydrolysis resistance, and the two coatings also show better synergistic effect.

[0086] In Example 10, PP (polypropylene) resin is added to form a multi-polymer blend system, which improves the impact resistance and processing performance of the material. The addition of PP resin effectively improves the processing fluidity of the material. At the same time, since PP resin has high impact resistance, a tough phase is formed in the material, which enhances the impact toughness and fatigue resistance of the overall structure.

[0087] In Example 11, HDPE (high-density polyethylene) resin is further added to enhance the mechanical properties and chemical resistance of the material. In the new formula, the synergistic effect of PP resin and HDPE resin forms a more compact polymer network structure. The high crystallinity of HDPE resin and the toughness of PP resin combine to produce excellent stress cracking resistance and environmental aging resistance. At the same time, PVDF has good compatibility with HDPE, which further improves the chemical resistance of the material.

[0088] Examples 11 to 15 show synergistic effects: (1) Synergy between PVDF, PFA and PEEK: Chemical stability synergy: PVDF and PFA are both fluorinated polymers with excellent chemical stability. The addition of PEEK further improves the heat resistance and acid and alkali resistance of the material. Under high temperature environment, the crystalline phase formed by these three polymers can effectively resist the damage of acid and alkali environment to the material structure.

[0089] Synergy of mechanical properties: PEEK has high rigidity and fatigue resistance, while PVDF and PFA have good flexibility and impact resistance. The combination of the three makes the material have both high rigidity and good impact toughness.

[0090] (2) Synergistic effect of boron nitride nanosheets and chopped fibers: Reinforcement and thermal conductivity synergy: Short-cut fibers, as a mechanical reinforcement phase, can disperse stress in the material and improve the tensile strength and impact resistance of the material. After being treated with silane coupling agents, the surface activity of boron nitride nanosheets and short-cut fibers is enhanced, and the interfacial bonding force with the matrix resin is increased, further improving the creep resistance and interfacial strength of the material.

[0091] Embodiment 7-embodiment 9: Microscopic crystal structure: PVDF, PFA and PEEK gradually crystallize at different temperatures to form a multi-level crystal structure.

[0092] Coating structure: The PTFE and FEP composite coatings in Examples 8 and 9 form a dense microstructure on the surface of the material, which prevents the penetration of moisture and chemical reagents and improves the chemical corrosion resistance and hydrolysis resistance of the material.

[0093] Example 10-Example 11: Polymer blend structure: The addition of PP resin and HDPE resin changes the microscopic phase distribution of the material, forming a dispersed nested structure. At the interface of the blend phase, the mutual entanglement between polymer segments enhances the toughness and creep resistance of the material, thereby enhancing the chemical resistance and hydrolysis resistance of the material.

[0094] Fiber-reinforced network: The chopped fibers form a randomly distributed reinforcement network in the material, which works together with the boron nitride nanosheets in the matrix to further enhance the chemical and hydrolysis resistance of the material.

[0095] Example 12-Example 15: Degradation of the polymer crystalline phase: With the removal of high-performance polymers (such as PVDF, PFA, and PEEK), the crystallinity of the material decreases and the internal microstructure becomes unstable. Chemical and thermal resistance are both reduced.

[0096] Lack of fillers: After removing the BN nanosheets or chopped fibers, the performance of the material decreased, indicating that these fillers play an important reinforcing role in the composites.

[0097] Finally, it should be noted that the above content is only used to illustrate the technical solution of the present invention, rather than to limit the scope of protection of the present invention. Simple modifications or equivalent substitutions of the technical solution of the present invention by ordinary technicians in this field do not deviate from the essence and scope of the technical solution of the present invention.

Claims

1. A large mesh high strength water inlet grid, characterized in that: The water inlet grid is prepared by the following steps: Weighing raw materials, the raw materials include base resin and additives, the additives include at least one of lubricant, antioxidant, nucleating agent and filler; The weighed raw materials are added to the extruder, melted, mixed and heated, and then extruded into shape: after the materials are fully melted and mixed, they pass through a specially designed large-mesh rotary die head to be integrally formed into a grid product, and then go through cooling and winding processes to obtain a water inlet grid; Among them, the specific parameters of the grid product formed into one piece through a specially designed large mesh rotary die include: Thickness: 20-50mil; Angle: 30-150°; Mesh area: 10-50mm 2 .

2. The large-mesh high-strength water inlet grid according to claim 1 is characterized in that: By weight, the base resin is 80-110 parts; the lubricant is 0-0.5 parts; the antioxidant is 0.1-0.5 parts; the nucleating agent is 0-5.0 parts; and the filler is 0-10 parts.

3. The large-mesh high-strength water inlet grid according to claim 1, characterized in that: The base resin includes at least one of PP resin, HDPE resin, PVDF, PFA, and PEEK; the lubricant includes PE wax; the antioxidant includes a hindered phenol antioxidant; and the filler includes at least one of talc powder, boron nitride nanosheets, and chopped fibers.

4. The large-mesh high-strength water inlet grid according to claim 1, characterized in that: The temperature of the extruder melt mixing heating is controlled at 200-300°C.

5. The large-mesh high-strength water inlet grid according to claim 1, characterized in that: The raw materials further include a silane coupling agent, and the antioxidant includes at least one of antioxidant 1010 and antioxidant 168 .

6. The large-mesh high-strength water inlet grid according to claim 1, characterized in that: When adding the weighed raw materials into the extruder, different temperature sections of 260-320℃ are set to blend the base resin, and then the remaining raw materials are added in the mixing stage. The extruder melts, mixes and heats the materials, and then extrude them into shape: after the materials are fully melted and mixed, they pass through a specially designed large-mesh rotary die head to be integrally formed into a grid product, and then go through cooling and winding processes to obtain a water inlet grid.

7. The large-mesh high-strength water inlet grid according to claim 1, characterized in that: The preparation steps also include: after extrusion molding, applying a coating on the surface of the water inlet grid: using plasma spraying equipment to spray the coating solution on the water inlet grid, after spraying, curing the water inlet grid at 100-150°C for 20-60 minutes to obtain a finished grid.

8. The large-mesh high-strength water inlet grid according to claim 7, characterized in that: The coating solution includes at least one of PTFE, a fluorinated solvent, an accelerator, NMP, FEP, and a dispersant.

9. The large-mesh high-strength water inlet grid according to claim 7, characterized in that: The coating solution includes coating solution 1 and coating solution 2, Mix PTFE and fluorinated solvent, stir evenly, add accelerator, and stir to obtain coating solution 1; Heat NMP to 150-180° C., gradually add FEP, stir, add accelerator, then add dispersant, stir, slowly cool the uniformly mixed solution to room temperature at 80-100° C., stirring during the process, to obtain coating solution II.

10. The large-mesh high-strength water inlet grid according to claim 9, characterized in that: After extrusion molding, a coating is applied on the surface of the water inlet grid: a plasma spraying device is used to spray coating solution 1 on the water inlet grid. After spraying, the water inlet grid is cured at 100-150°C for 20-60 minutes to obtain a cured grid; a plasma spraying device is used to spray coating solution 2 on the cured grid. After spraying, the water inlet grid is cured at 100-150°C for 20-60 minutes to obtain a finished grid.

Citation Information

Patent Citations

  • Self-support PVDF (polyvinylidene fluoride) homogeneous micropore tubular membrane as well as preparation method thereof

    CN103933873A

  • Water inlet separation net with smooth surface and preparation method of water inlet separation net

    CN116903950A

  • Spiral reverse osmosis membrane element and separation method

    JP3052958B1

  • Methods of making and using liquid filter media

    US20120248034A1

  • Separation membrane element and operation method therefor

    US20190282962A1